The legality of political strikes in collective labor law: A perspective of Taiwanese labor law - Sheng-Hung Luo; Yun-Hao Chuang (Journal of Law Science, 2026)
This article analyzes the legality of political strikes in the framework of collective labor law, focusing on the Taiwanese legal system. The right to strike assists workers in addressing structural economic disadvantages; however, the legal status of political strikes in Taiwan remains contentious. Prior studies have not methodically examined the interplay between political demands and the existing framework of strike legality. This study utilizes a doctrinal legal methodology to analyze the Act for Settlement of Labor-Management Disputes and related legal materials, including judicial interpretations, academic literature, and comparative analyses from Germany, Japan, the United States, and international labor law, with a specific focus on the jurisprudence of the International Labour Organization (ILO). The research indicates that Taiwanese law predominantly permits strikes intended to enhance working conditions. Consequently, purely political strikes are generally considered illegitimate because their demands target the state instead of the employer, and their goals extend beyond the immediate improvement of labor conditions. Nonetheless, the research demonstrates that socio-economic political strikes related to workers' economic interests exist in a hybrid state that a categorical prohibition cannot adequately address. The article clarifies the distinction between strike targets and strike purposes, thereby enriching the theoretical discussion on the classification of political strikes. It asserts that demonstrative political strikes linked to socio-economic labor interests should be evaluated according to the principles of proportionality and last resort. This method helps us check if political strikes are legal in a more organized way while keeping the collective bargaining system stable.